Development of an itraconazole encapsulated polymeric nanoparticle platform for effective antifungal therapy. Issue 10 (15th February 2016) - Ling, Xiang; Huang, Zewei; Wang, Jianzhao; Xie, Jiarong; Feng, Min; Chen, Yang; Abbas, Farhana; Tu, Jiasheng; Wu, Jun; Sun, Chunmeng
Abstract : Schematic illustration of the construction and in vivo trafficking of ITZ-NPs. Abstract : This study is to develop a novel itraconazole-loaded nanoparticle (ITZ-NP) platform for effective antifungal therapy. First, the monomethoxypoly(ethylene glycol)- b -poly(lactic acid) (mPEG- b -PLA) copolymer was prepared as a drug carrier material. Then the nanoparticles were formulated via a simple film hydration method. The copolymer and nanoparticles were characterized by standard methods, including 1 H NMR, 13 C NMR, FT-NIR, DSC, XRPD, and particle size, zeta potential, morphology and physical examination. Furthermore, in vitro itraconazole release and antifungal activity were intensively evaluated. The results showed that the formed nanoparticles significantly enhanced sustained drug release and inhibited fungal infection. In addition, ITZ-NPs caused very mild hemolysis and slight venous irritation, indicating much better biocompatibility than marketed cyclodextrin formulations of ITZ. An Iin vivo biodistribution study via intravenous injection showed that ITZ-NPs could be effectively retained in blood circulation and selectively distributed in RES-rich organs compared with commercial cyclodextrin injection, with the verification of Re, Te, R Te and Ce. In summary, the developed ITZ-NPs could reduce systemic toxicity, improve antifungal activity and act as a potential intravenous formulation of ITZ.